Some causes and consequences of lithospheric thinning in the eastern North China Craton : evidence from latest Yanshanian granitoids and dykes - Goss, Sarah Catherine (Curtin University, 2010)
The lithosphere beneath the eastern part of the North China Craton (NCC) is known to have been thick (> 200 km) during the Early Palaeozoic as manifested by the presence of diamondiferous kimberlites (Menzies et al., 1993; Griffin et al., 1998; Yang et al., 2009). However, in the Cenozoic we know it was much thinner (75-80 km) as implied by the presence of spinel-facies xenoliths in the alkali basalts, as well as evidence from geophysical investigations such as seismic data and heat flow measurements (Yuan, 1996; Menzies and Xu, 1998; Gao et al., 2002; Zhou et al., 2002; Wu et al., 2005b; Yang et al., 2009). This has lead to the assumption that at some stage during the Mesozoic, part or all, of the lithospheric mantle keel was thinned or lost (Menzies et al., 1993; Wilde et al., 2003; Gao et al., 2004; Wu et al., 2005a; Liu et al., 2008d).The exact timing and mechanism of this thinning has been a hot topic of research for some time and there is still ongoing debate. By analysing key rock units in Shandong Province in the eastern part of the NCC, this research thesis aims to establish a more accurate temporal history of the area, including how the nature and composition of the lithospheric mantle evolved during the Mesozoic. The emphasis has been on determining the differences in the geochemical signatures of selected magmatic rocks to determine the state of the lithospheric mantle at various times and depths. The granitoids that form Paper 1 (Chapter 2) were chosen because they were thought to be the youngest Late Yanshanian intrusions in the area (SBGMR, 1991; Zhao et al., 1998b; Zhou and Lu, 2000) and would provide information about the nature of the lower crust and mantle in the Early Cretaceous. The felsic, intermediate, mafic and lamprophyric dykes of Paper 2 (Chapter 3) were selected with the aim of determining if there was a spatial or temporal pattern in lithospheric evolution across the region that could be related to a distinct mechanism of thinning.Based on the research carried out in this thesis it is confirmed that the granitoids selected are indeed younger than the more typical Late Yanshanian granitoids. The ages of the sampled intrusions range from 118 ± 1 Ma to 113 ± 2 Ma and they represent a continuation of the extensional regime in the Early Cretaceous. The geochemistry of the granitoids suggest that they were derived from partial melting of older continental crust due to mafic magma underplating, followed by various degrees of interaction between mantle-derived mafic magma and felsic crustal magma. The dykes range in age from 114 ± 1 Ma to 105 ± 2 Ma. The geochemistry of the dykes suggests that the lithospheric mantle beneath the eastern NCC had an enriched nature during their intrusion in the Early Cretaceous. The generation of both these magmatic rock groups provide evidence of asthenospheric upwelling, lithospheric extension and interaction between the crust and mantle during the Mesozoic.A model to explain the genesis of both the granitoids and the dykes, also consistent with the various Mesozoic tectonic events, has been developed. The conclusion is that subduction of the Pacific Plate beneath the eastern NCC, followed by slab roll-back, was the dominant driving force that led to extension, lithospheric thinning and delamination. These in turn resulted in asthenospheric upwelling and generation of basaltic magmas that were either emplaced into the lower crust as dykes (Paper 2/Chapter 3), or were underplated beneath the crust, causing partial melting and generation of the granitoids (Paper 1/Chapter 2).The delamination of the NCC lithosphere during the Cretaceous can explain how the whole of eastern Asia, including the eastern and central NCC, the South China Craton (SCC) and the Central Asian Orogenic Belt (CAOB), were affected by extension, widespread magmatic activity and lithospheric thinning at this time (Zhou and Li, 2000; Fan et al., 2003; Zhang et al., 2003d; Wu et al., 2005a).